2020
DOI: 10.3390/molecules25030598
|View full text |Cite
|
Sign up to set email alerts
|

Xanthones, A Promising Anti-Inflammatory Scaffold: Structure, Activity, and Drug Likeness Analysis

Abstract: Inflammation is the body’s self-protective response to multiple stimulus, from external harmful substances to internal danger signals released after trauma or cell dysfunction. Many diseases are considered to be related to inflammation, such as cancer, metabolic disorders, aging, and neurodegenerative diseases. Current therapeutic approaches include mainly non-steroidal anti-inflammatory drugs and glucocorticoids, which are generally of limited effectiveness and severe side-effects. Thus, it is urgent to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 86 publications
1
31
0
Order By: Relevance
“…Besides being non-toxic in nature they are considered to less expensive [18,19,20 21,22,23,24,25,26,27,28] . Seaweeds in general and red algae in particular have been reported for their potential role as potent anti-inflammatory and anticancer because of their rich and unique constituents [58,59,60], which agrees well with the present study findings ( Table 1). The present study revealed the presence of different secondary metabolites such as marine Xanthones which exhibit wide spectrum of activities such as anti-cancer, anti-inflammatory, anti-diabetic etc.…”
Section: Impact Of G Oblongata On the Inflammatory Biomarkerssupporting
confidence: 93%
“…Besides being non-toxic in nature they are considered to less expensive [18,19,20 21,22,23,24,25,26,27,28] . Seaweeds in general and red algae in particular have been reported for their potential role as potent anti-inflammatory and anticancer because of their rich and unique constituents [58,59,60], which agrees well with the present study findings ( Table 1). The present study revealed the presence of different secondary metabolites such as marine Xanthones which exhibit wide spectrum of activities such as anti-cancer, anti-inflammatory, anti-diabetic etc.…”
Section: Impact Of G Oblongata On the Inflammatory Biomarkerssupporting
confidence: 93%
“…To better compare those anti-inflammatory clerodane diterpenoid derivatives with marketed drugs, the MW, HBA, HBD [ 98 ], Log P, PSA, RB, and stereogenic centers were evaluated; and the marketed drugs were divided into natural products, natural products derivatives, natural product type macrocycles, polycyclic compounds, synthetic compounds, and assumed synthetic compounds [ 99 , 100 ] (Fig. 3 ).…”
Section: Comparison Of Drug-likeness Of Anti-inflammatory Clerodane Dmentioning
confidence: 99%
“…Many reviews to date discuss on various biological activities of xanthones (Ibrahim et al, 2016;Aizat et al, 2019;Feng et al, 2020;Ong et al, 2020) with a recent review discussing the modulatory ability of xanthones on macrophage function and associated inflammatory diseases (Ng and Chua, 2019). The reviews on the potential of xanthones as anti-inflammatory agents for skin diseases are limited and no review has been focused extensively on their mechanisms of action in the context of skin inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%